Solvothermal orthorhombic Sb2S3 nanobars: Effect of hydrothermal temperature in properties for solar cell application - E.M. Mkawi (Results in Physics, 2020)
In this work we will report on the preparation and study of good quality phase-pure Sb2S3 nanobars fabricated through a solvothermal method from solution containing SbCl3 and Na2S2O3. The influence of hydrothermal temperatures (Ht = 200,210,220 and 230 °C) on the structural, morphological and compositional properties of the nanobars were investigated using XRD, XPS, Raman, TEM, FESEM and UV spectroscopy. X-ray diffraction and Raman results demonstrated an improvement in crystallinity, a Sb2S3 nanobars that was high purity and belonging to the orthorhombic phase. At an Ht = 230 °C, EDX spectrometry analysis peaks showed perfect stoichiometry for an atomic ratio of 2:3 for Sb: S. TEM results indicated that the appearance of the fabricated Sb2S3 was nanobar-like and grew along the [001] direction. Sb2S3 thin film base nanobars showed compact and smooth surfaces without pinholes or cracks with a grain size 1–3 µm. The optical absorption coefficient was more than 104 cm−1 leading to an optical energy gap (Eg) of 1.55 eV. A solar cell, glass/FTO/ Sb2S3/ CdS/ZnO/Ag, prepared with a Sb2S3 nanobars base thin film had a Voc = 451 mV, Jsc = 12.5 mA/cm2, FF = 62.8 and a solar energy conversion efficiency of 3.54%.